PENGARUH PRODUK DOMESTIK REGIONAL BRUTO, PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP BELANJA MODAL DI KOTA BALIKPAPAN - Hartati, Hariani Dwi (Faculty of Economics and Business, University of Muhammadiyah Malang, 2013)
This project was designed to: 1) explore the effects of Gross Domestic Product (GDP), Own-source Revenue (PAD), and government transfer payments to local capital expenditures, both partially and simultaneously; 2) find out the dominant variable which affected the local capital expenditure in Balikpapan. The data, which was obtained through literature review study, were in the type of secondary and time series records derived during the period of 2002-2011. Further, these files were analyzed by implementing multiple linear regressions with three predictors technique, where the assumption tests was applied earlier presently before the main analysis. Eventually, the results showed that: 1) GDP, Local Revenue and government transfer payments gave significant impact on local capital expenditures of Balikpapan simultaneously. a) GDP has considerable effect on local capital expenditures partially; b) local revenue has not extensively influence the local capital expenditure to some extent; c) the government transfer payments has not much influence on the local capital expenditure in some measure. 2) GDP was the most dominant variable affecting the local capital expenditures.